Effects of Supplementing Finishing Goats with Mitragyna speciosa (Korth) Havil Leaves Powder on Growth Performance, Hematological Parameters, Carcass Composition, and Meat Quality - Pin Chanjula; Juraithip Wungsintaweekul; Rawee Chiarawipa; Kampanat Phesatcha; Chanon Suntara; Rittikeard Prachumchai; Patcharin Pakdeechanuan; Anusorn Cherdthong (Animals, 2022)
The objective of this study was to see how dried Mitragyna speciosa Korth leaves (DKTL) affected growth, hematological parameters, carcass characteristics, muscle chemical composition, and fatty acid profile in finishing goats. In a randomized complete block design, twenty crossbred males (Thai Native x Boer) weaned goats (17.70 ± 2.50 kg of initial body weight (BW)) were provided to the experimental animals (5 goats per treatment) for 90 days. Individual dietary treatments of 0, 2.22, 4.44, and 6.66 g/d of DKTL on a dry matter basis were given to the goats. The diets were provided twice daily as total mixed rations ad libitum. In comparison to the control diet, DKTL supplementation had no effect on BW, average daily gain (ADG), feed conversion ratio (FCR), carcass composition, meat pH, or meat color (p > 0.05). After DKTL treatment, the hot carcass weight, longissimus muscle area, oleic acid (C18:1n9), monounsaturated fatty acid (MUFA), and protein content increased, but saturated fatty acids (SFA) and ether extract decreased (p < 0.05). To summarize, DKTL supplementation can improve goat meat quality.